Gender Dynamics in Transboundary Water Governance: Feminist Perspectives on Water Conflict and Cooperation - Jenniver Sehring; Rozemarijn ter Horst; Margreet Zwarteveen (Routledge, 2022)
This volume assesses the nexus of gender and transboundary water governance, containing empirical case studies, discourse analyses, practitioners' accounts, and theoretical reflections. Transboundary water governance exists at the intersection of two highly masculinised fields: diplomacy and water resources management. In both fields, positions are mainly held by men, and core ideas, norms, and guiding principles that are presented as neutral, are both shaped by men and based on male experiences. This book sheds light on the often hidden gender dynamics of water conflict and cooperation at the transboundary level and on the implicit assumptions that guide research and policies. The individual chapters of the book, based on case studies from around the world, reveal the gendered nature of water diplomacy, take stock of the number of women involved in organisations that govern shared waters, and analyse programmes that have been set up to promote women in water diplomacy and the obstacles that they face. They explore and contest leading narratives and knowledge that have been shaped mainly by privileged men, and assess how the participation of women concretely impacts the practices, routines, and processes of water negotiations. This volume will be of great interest to students and scholars of water governance, water diplomacy, gender, international relations and environmental politics. It will also be of interest to professionals and policymakers involved in supporting gender mainstreaming in water cooperation.
Keywords: 340; Development economics and emerging economies; Applied ecology; The Earth: natural history: general interest; Environmental management; Diplomacy; Environmental policy and protocols; Environmental science; engineering and technology; Feminism and feminist theory; Gender studies; gender groups